2020
DOI: 10.1002/anie.202002366
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Structural Characterization of Eightfold Protonated Octacyanometalates [M(CNH)8]4+ (M=MoIV, WIV) from Superacids

Abstract: Octacyanometalates K4[Mo(CN)8] and K4[W(CN)8] are completely protonated in superacidic mixtures of anhydrous hydrogen fluoride and antimony pentafluoride. The resulting hydrogen isocyanide complexes [Mo(CNH)8]4+ [SbF6]−4 and [W(CNH)8]4+ [SbF6]−4 are the first examples of eight‐coordinate homoleptic metal complexes containing hydrogen isocyanide (CNH) ligands. The complexes were crystallographically characterized, revealing hydrogen‐bonded networks with short N⋅⋅⋅H⋅⋅⋅F contacts. Low‐temperature NMR measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Hence, super acids are a common medium to stabilize transition metal complexes in unusually high oxidation states in general. 12 Likewise, reductive carbonylation in super acidic mixtures like fluoroantimonic acid (HF/SbF 5 ) or “magic acid” (HSO 3 F/SbF 5 ) was utilized by Willner and Aubke to yield several diamagnetic 14, 16 & 18 valence electron (VE) TMCCs containing mono-to trivalent metals. 7 Yet, this system is limited by the coordination ability of the [SbF 6 ] − anion, which is incompatible with the strong fluorophilicity of early transition metals 13,14 as well as the strong acidity, which obstructs Brønsted basic TMCs as starting materials.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, super acids are a common medium to stabilize transition metal complexes in unusually high oxidation states in general. 12 Likewise, reductive carbonylation in super acidic mixtures like fluoroantimonic acid (HF/SbF 5 ) or “magic acid” (HSO 3 F/SbF 5 ) was utilized by Willner and Aubke to yield several diamagnetic 14, 16 & 18 valence electron (VE) TMCCs containing mono-to trivalent metals. 7 Yet, this system is limited by the coordination ability of the [SbF 6 ] − anion, which is incompatible with the strong fluorophilicity of early transition metals 13,14 as well as the strong acidity, which obstructs Brønsted basic TMCs as starting materials.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported that eight-fold protonation of [M(CN)8] 4− (M=Mo, W) to the corresponding [M(CNH)8] 4+ tetracations is achieved under superacidic conditions by a combination of anhydrous hydrogen fluoride with the super Lewis acid SbF5. 21 Similarly, the combination of MeF with AsF5 in liquid SO2 as solvent is known to generate the extremely powerful methylating agent [MeOSO][AsF6]. 22 However it has been rarely used in recent times.…”
Section: Introductionmentioning
confidence: 99%